Funcionarios. (UNED, 2024)
De izquierda a derecha de pie Javier Sandí Méndez, Carlos Guerrero Echavarria, Victor Raúl Solano Núnez, Mario Barquero Chacón, Víctor Díaz Chinchilla, Franklin Villalobos Salas, Luis Carlos Huertas Acuña